PARENTAL AND PEER ATTACHMENT AS DETERMINANT FACTORS OF ADOLESCENT’S OPTIMISM - Yulian Hadi; Alfiasari (Journal of Child, Family, and Consumer Studies, 2023)
An optimistic life is important to everyone. An external factors that contributes to life optimism of adolescent are interactions with parents and peers. This study aims to analyze the influence of adolescent’s and family’s characteristics and parental and peer attachment on adolescent's optimism in life. This study used a cross-sectional research method in senior high schools and vocational schools located in Bekasi City, West Java. Total of 256 students were participated in the study. The results showed that most adolescents had a secure attachment to their parents and peers,and a high degree of optimism in life. The study also found that parent-child attachment has a significant positive relationship and influence on teeanger's life optimism. Further analysis showed that the mother-peer attachment model had a higher influence on teeanger's life optimism than the father-peer attachment model, although both models has significant influence.